'Basic and Applied Thermogenesis Research' Bridging the Gap. (January 2018) - Carobbio, Stefania; Guénantin, Anne-Claire; Vidal-Puig, Antonio
Abstract : Obesity is a major health problem without satisfactory pharmacological treatment. A promising strategy is to promote energy dissipation by activating brown/beige adipose tissue. However, for this strategy to succeed it requires improving the transferability amongst cellular, murine, and human systems and bridging the gap between basic and clinical research.